Mr. Wolf's class. Lucky stars - Steinke, Aron Nels (New York : Graphix, 2019)
Mr. Wolf's students are having a 'writer's workshop' and are learning about personal narratives. Sampson doesn't think anything worth writing has ever happened to him. But when he and Margot go for a bike ride one morning, he has an accident that gives him a new perspective, and he thanks his lucky stars that he's going to be okay. Meanwhile, Penny gives the rats at school treats so that they'll leave gifts for her, and Stewart and Oliver try to learn how to get along at recess.
3.1
3-6
GN470L
Keywords: Elementary school teachers -- Comic books, strips, etc. -- Juvenile fiction; Schools -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Humorous stories; Elementary school teachers -- Fiction; Schools -- Fiction; Friendship -- Fiction; Humorous stories; Cartoons and comics; Humorous comics; Graphic novels